Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1097/shk.0000000000001774
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Elevated Systolic Blood Pressure and Outcomes in Critically Ill Patients: A Retrospective Cohort Study and Propensity Analysis

Abstract: Introduction: Studies have shown nonlinear relationships between systolic blood pressure (SBP) and outcomes, with increased risk observed at both low and high blood pressure levels. However, the relationships between cumulative times at different SBP levels and outcomes in critically ill patients remain unclear. We hypothesized that an appropriate SBP level is associated with a decrease in adverse outcomes after intensive care unit (ICU) admission. Methods: This study was a retrospective analysis of data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…1 PRISMA flow diagram of included studies. Of the two articles analyzing the Medical Information Mart for Intensive Care (MIMIC) cohort and reporting data on mortality [ 8 , 20 ], one could be included in the meta-analysis [ 8 ]. The article with the highest NOS score was used in the summary table [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 PRISMA flow diagram of included studies. Of the two articles analyzing the Medical Information Mart for Intensive Care (MIMIC) cohort and reporting data on mortality [ 8 , 20 ], one could be included in the meta-analysis [ 8 ]. The article with the highest NOS score was used in the summary table [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…[19,20] BP has been shown to be an important determinant of adverse cardiovascular events in patients. [18] Data from a small retrospective study of patients with cardiogenic shock concluded that, of several hemodynamic parameters, only DPB (particularly DPB < 40 mm Hg in the 24 hours prior to ICU P value: as for the difference between survivors and non-survivors; Kruskal-Wallis test was applied for the variables with a skewed distribution. DBP = diastolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that there was a nonlinear association between baseline DBP and in-hospital death among patients with AMI, with increased risk observed at both low and high BP values. [ 18 ] Moreover, the DBP that was dynamic during the first 3 days of ICU stay also seems to be a meaningful prognostic factor in patients with AMI. We discovered that DBP in the deaths decreased within the first 3 days after ICU stay, but the changes in DBP of the surviving group were smaller and slower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is uncertain above which BP level the risk of AF is significantly increased. Also, the extent to which BP control reduces AF in hypertensive patients is unknown, despite clear evidence that BP control reduces target organ damage and improves overall survival ( 9 11 ). Though some researches demonstrated an ideal BP in patients with AF ( 12 ), most current HBP guidelines do not specify BP-lowering goals for patients with AF ( 13 – 16 ).…”
Section: Introductionmentioning
confidence: 99%